2019
DOI: 10.1002/jia2.25279
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes after implementation of treat all in Rwanda: an interrupted time series study

Abstract: Introduction Nearly all countries in sub‐Saharan Africa have adopted policies to provide antiretroviral therapy ( ART ) to all persons living with HIV (Treat All), though HIV care outcomes of these programmes are not well‐described. We estimated changes in ART initiation and retention in care following Treat All implementation in Rwanda in July 2016. Methods We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
3
26
1
Order By: Relevance
“…Similar to other studies , younger age, being unmarried and clinical factors (BMI, haemoglobin, creatinine) increased the risk of adverse outcomes in both health zones and irrespective of disease progression. In contrast to another setting , the level of education did not show associations.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to other studies , younger age, being unmarried and clinical factors (BMI, haemoglobin, creatinine) increased the risk of adverse outcomes in both health zones and irrespective of disease progression. In contrast to another setting , the level of education did not show associations.…”
Section: Discussionsupporting
confidence: 86%
“…However, this is unlikely as missing data mainly occurred at two clinics, which had similar CD4 count distributions to the other six clinics. Staff may have placed less emphasis on CD4 count testing as it was no longer required to guide ART eligibility; a phenomenon reported in other programmatic studies of Treat All [6]. Additionally, in a South African study, the main reasons for missing CD4 testing appeared to be independent of CD4 count (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Treat All has now been implemented in the majority of LMICs [2], but there is limited data regarding the impact on treatment outcomes in public sector ART programmes [6,7]. In these settings, there has been concern that asymptomatic PLHIV with high CD4 counts could be less motivated to remain in care and adhere to treatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other implementation studies conducted to date comparing outcomes before and after "Treat All" [6][7][8][9][10][11][12][13], our study sample size was large. The pilot districts were distributed across all the regions of the country.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Multiple studies have assessed the realworld effects of "Treat All" on ART initiation, linkage, virologic suppression, and retention. However, these studies have reported inconsistent results [6][7][8][9][10][11][12][13]. None of these previous studies has assessed if predictors for attrition changed since the transition to "Treat All".…”
Section: Introductionmentioning
confidence: 99%